Is Adherence to 24-Hour Movement Guidelines Associated with a Higher Academic Achievement Among Adolescent Males and Females? - Garcia-Hermoso, A (Elsevier Ltd, 2022)
Objectives: This study aims to examine the independent and combined associations of 24-Hour Movement Guidelines for physical activity, screen time, and sleep duration with academic achievement in adolescent males and females. Design: Cross-sectional study. Methods: 1290 Spanish adolescents (565 females), aged 11 to 16 years (13.06 ± 0.84), participated in this study. Self-reported physical activity, screen time, and sleep duration questionnaires were assessed. Academic achievement was calculated as an average score of the adolescents’ grades in first language (Spanish), first foreign language (English), and mathematics subjects. A multiple linear regression model was used to examine the association between meeting 24-Hour Movement Guidelines and academic achievement. Covariates included age, sex, socioeconomic status, body mass index, and cardiorespiratory fitness. Results: Not meeting any of the three 24-Hour Movement Guidelines was associated with lower academic achievement in the whole sample (p < 0.001). Meeting physical activity and sleep duration guidelines, both independently and together, was associated with higher academic achievement in the whole sample (p < 0.001). Meeting at least two recommendations was associated with higher academic achievement in males (p < 0.01). However, trend analysis revealed that participants who met two or three recommendations had higher academic achievement compared to those who met one or none of these recommendations (p < 0.05). All these results were similar for males and females. Conclusions: Our findings suggest the importance of promoting more than one 24-Hour Movement Guidelines, mainly physical activity and sleep duration, which seems to contribute positively to increased academic performance in adolescents. © 2021 The Author(s)